Perlindungan Hukum Terhadap Pihak Ketiga Atas Perjanjian Perkawinan Yang Dibuat Setelah Perkawinan - Yudiana Dewi Prihandini (Lex Renaissance, 2019)
This study aims to formulate legal protection efforts for third parties if the marriage agreement is made after the marriage. This is derived from the Constitutional Court Decision Number 69 / PUU-XII / 2015 that defines the marriage agreement to be expandable, so that the marriage agreement is no longer interpreted only as an agreement made before the marriage (prenuptial agreement) but can also be made after the marriage takes place (postnuptial agreement). The Constitutional Court’s decision can lead to legal problems and legal uncertainty for third parties. This relates to the execution carried out by the creditor in the event of an agreement to separate property and unclear parties responsible when there is a default. This research is a normative legal study with the statutory and case approach. This study concludes, firstly, the Constitutional Court Decision Number 69 / PUU-XII / 2015 regarding marriage agreements can lead to rights and obligations and consequences for the parties. Second, in order to guarantee legal protection for third parties, the making and amendment of the marriage agreement should be carried out before a notary, made in good faith by the parties, must be recorded by the marriage registrar.